Literature and weather : Shakespeare - Goethe - Zola - Ungelenk, Johannes (Spectrum Literaturwissenschaft / spectrum Literature ;, 2018)
""Literature and Weather. Shakespeare -- Goethe -- Zola" is dedicated to the relation between literature and weather, i.e. a cultural practice and an everyday phenomenon that has played very different epistemic roles in the history of the world. The study undertakes an archaeology of literature's affinity to the weather which tells the story of literature's weathery self-reflection and its creative reinventions as a medium in different epistemic and social circumstances. The book undertakes extensive close readings of three exemplary literary texts: Shakespeare's The Tempest, Goethe's The Sufferings of Young Werther and Zola's The Rougon-Macquarts. These readings provide the basis for reconstructing three distinct formations, negotiating the relationship between literature and weather in the 17th, the 18th and the 19th centuries. The study is a pioneering contribution to the recent debates of literature's indebtedness to the environment. It initiates a rewriting of literary history that is weather-sensitive; the question of literature's agency, its power to affect, cannot be raised without understanding the way the weather works in a certain cultural formation"--